2013
DOI: 10.1007/s11064-013-1175-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prolyl Hydroxylase Inhibitor Protects Against Cell Death After Hypoxia

Abstract: Hypoxia-inducible factor 1 (HIF-1) is regulated by the oxygen-dependent hydroxylation of proline residues by prolyl hydroxylases (PHDs). We recently developed a novel PHD inhibitor, TM6008, that suppresses the activity of PHDs, inducing continuous HIF-1α activation. In this study, we investigated how TM6008 affects cell survival after hypoxic conditions capable of inducing HIF-1α expression and how TM6008 regulates PHDs and genes downstream of HIF-1α. After SHSY-5Y cells had been subjected to hypoxia, TM6008 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A more suitable approach may be through a recently identified novel class of PHD inhibitor [129], which acts by preferential binding directly to the PHD active sites. One of these novel inhibitors, TM6008, was observed to reduce cell death after hypoxic exposure [130]. Therefore, TM6008 may have potential to reduce the IL-1α driven inflammation that is associated with necrotic cell death in hypoxic disease [27].…”
Section: Hif-1αmentioning
confidence: 99%
See 1 more Smart Citation
“…A more suitable approach may be through a recently identified novel class of PHD inhibitor [129], which acts by preferential binding directly to the PHD active sites. One of these novel inhibitors, TM6008, was observed to reduce cell death after hypoxic exposure [130]. Therefore, TM6008 may have potential to reduce the IL-1α driven inflammation that is associated with necrotic cell death in hypoxic disease [27].…”
Section: Hif-1αmentioning
confidence: 99%
“…Therapies to prevent or alleviate inflammation driven by hypoxia are in early stages of trials, or have previously shown no significant clinical effect. However, these studies used relatively crude clinical endpoints and none have yet been investigated as interventions to prevent the onset of structural lung disease [105,106,110,119,130]. Currently, the majority of targets for therapy are involved in the initial activation of the inflammatory pathway, but there is little research into activators further downstream in the pathway (figure 3).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Current hypoxia mimics are also nonspecific in that they act to modulate function of a large class of 2OG-dependent hydroxylases possibly leading to unwanted effects. This has led to the discovery of PHD2-specific inhibitors synthesised through three-dimensional enzymatic modelling (Refs 136, 137). These molecules have yet to be tested in the context of bone biology.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…TM6008 has been shown to be efficacious in the treatment of inflammatory diseases, because PHD2 inhibition by TM6008 suppressed tumor necrosis factor-α mediated inflammation in macrophages [58]. A recent study further implicated TM6008 in enhancing cell survival after hypoxia by suppressing the protein expression of PHD2 and p53 [59].…”
Section: Development Of Phd Inhibitorsmentioning
confidence: 99%